At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 2x + 3 \)[/tex], we need to follow these steps:
1. Rewrite the function in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x + 3 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x + 3 \][/tex]
Subtract 3 from both sides:
[tex]\[ y - 3 = 2x \][/tex]
Divide both sides by 2:
[tex]\[ x = \frac{y - 3}{2} \][/tex]
3. Express the inverse function [tex]\( f^{-1}(x) \)[/tex]:
To rewrite our equation properly in the inverse function format, replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex]:
[tex]\[ f^{-1}(x) = \frac{x - 3}{2} \][/tex]
4. Simplify the inverse function:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Now, let's compare this function with the given options:
- [tex]\( f^{-1}(x) = -\frac{1}{2}x - \frac{3}{2} \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \)[/tex]
- [tex]\( f^{-1}(x) = -2x + 3 \)[/tex]
- [tex]\( f^{-1}(x) = 2x + 3 \)[/tex]
The correctly simplified inverse function is:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Hence, the correct answer is:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
1. Rewrite the function in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x + 3 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x + 3 \][/tex]
Subtract 3 from both sides:
[tex]\[ y - 3 = 2x \][/tex]
Divide both sides by 2:
[tex]\[ x = \frac{y - 3}{2} \][/tex]
3. Express the inverse function [tex]\( f^{-1}(x) \)[/tex]:
To rewrite our equation properly in the inverse function format, replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex]:
[tex]\[ f^{-1}(x) = \frac{x - 3}{2} \][/tex]
4. Simplify the inverse function:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Now, let's compare this function with the given options:
- [tex]\( f^{-1}(x) = -\frac{1}{2}x - \frac{3}{2} \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \)[/tex]
- [tex]\( f^{-1}(x) = -2x + 3 \)[/tex]
- [tex]\( f^{-1}(x) = 2x + 3 \)[/tex]
The correctly simplified inverse function is:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Hence, the correct answer is:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{3}{2} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.